Effect of thermal annealing and irradiation damage on the superconducting critical temperature of nanocrystalline gamma-Mo2N thin films - Haberkorn, Nestor Fabian (2019)
We report on the influence of the disorder and stoichiometry in the resulting superconducting critical temperature of γ-Mo2N thin films. Initially, three films (with Tc values of 7.6 K, 6.8 K and 6 K) were grown at room temperature by reactive sputtering, on Si (1 0 0) using different N2/(Ar+N2) mixtures. The influence of the thermal annealing up to 973 K and irradiation damage produced by 1 MeV Zr+(fluence up 2 × 1014 cm−2) is analyzed. The Tc of pristine films remains unchanged for increasing irradiation doses up 2 × 1014 cm−2. The Tc for annealed films decreases close to the value expected for bulk samples (≈5 K) for increasing the annealing temperature. Successive irradiations of the annealed films tend to increase their Tc up to its initial values (before annealing). The results indicate that the Tc in nanometric grain size γ-Mo2N thin films is affected by both nitrogen stoichiometry and disorder at the atomic scale.